EVT711: Air Pollution Control Technology / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (Universiti Teknologi MARA (UiTM), 2020)
This course deals with pollutant sources and their formation; atmospheric dispersion of pollutants; control of particulate and gaseous pollutants, volatile organic compounds, carbon monoxide, oxides of nitrogen and sulphur, etc. by techniques using devices such as filtration, scrubbers, condensers, electrostatic precipitators, incinerators, and absorption and adsorption units. Combustion related pollutants especially NOx and their control are also dealt with. Recent approaches to improve indoor air quality are also discussed.